Knowledge of reproductive rights and associated factors among Oda Bultum University students, eastern Ethiopia - Hussen, Amedin Mohammed; Usso, Ahmedin Aliyi; Agero, Gebi; Desalegn, Tewodros; Adem, Hassen Abdi; Yuya, Mohammed; Eyeberu, Addis; Sani, Adnan Abrahim (Frontiers in Reproductive Health, 2024)
BackgroundReproductive rights are an essential element of public health interventions to reduce adolescent and youth mortality and morbidity. A lack of knowledge about sexual and reproductive health is an important barrier that contributes to a variety of health and social issues. This study assessed the knowledge of reproductive rights among Oda Bultum University students, eastern Ethiopia.MethodsAn institution-based cross-sectional study was carried out among 727 students from December 1 to 30, 2020. Participants were selected using a multistage sampling technique. Data were collected using a self-administered, pre-tested, and structured questionnaire. Data were entered into EpiData version 4.1 and analyzed using SPSS version 27. The study employed both bivariable and multivariable logistic regression analysis to determine the variables associated with knowledge regarding reproductive rights. The significance and degree of strength were declared at a p-value < 0.05 using an adjusted odds ratio with a 95% confidence interval.ResultsThe overall knowledge of reproductive rights among university students was 47.2% (95% CI: 43.3%, 50.9%). Male gender (AOR = 2.11, 95% CI: 1.50, 2.97), urban residence (AOR = 1.62, 95% CI: 1.16, 2.28), formal maternal education (AOR = 2.26, 95% CI: 1.62, 3.17), participation in a sexual and reproductive health club (AOR = 2.67, 95% CI: 1.74, 4.10), utilization of sexual and reproductive health services (AOR = 6.29, 95% CI: 4.22, 9.36), and discussion about sexual and reproductive health issues (AOR = 1.60, 95% CI: 1.11, 2.30) were the factors that improved the knowledge of reproductive rights.ConclusionsAlmost half of the university students know about reproductive rights. Various factors identified were associated with the knowledge of reproductive rights among university students, including gender, residence, parental education level, engagement in sexual and reproductive health clubs, utilization of sexual and reproductive health services, and discussions about sexual and reproductive issues. Healthcare professionals at all levels should concentrate on offering excellent services related to reproductive health and establishing programs for specific education and counseling on reproductive rights for all well-behaved students.